Pengaruh Keterlibatan Merek, Komunikasi Merek, Dan Interaktivitas Merek Pada Keterikatan Merek Media Sosial - Nur Halimah Binti Abdul AZIZ; Susanto Susanto; Nonik Kusuma Ningrum (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to explain the effect of brand involvement, brand communication, and brand interactivity on brand engagement J.CO Indonesia Instagram. The population of this study is J.CO Donuts & Coffee customers, and the sample is J.CO Donuts & Coffee customers that follow company official Instagram. Using purposive sampling technique, a total of 120 respondents is asked to fill the questionaire as main survey data sources. The results show that partially Brand Involvement has a positive and significant effect on Social Media Brand Engagement, Brand Communication has a positive and significant effect on Social Media Brand Engagement, and Brand Interactivity has a positive and significant effect on on Social Media Brand Engagement, and simultaneously Brand Involvement, Brand Communication, and Brand Interactivity have a positive and significant effect on Social Media Brand Engagement.